Perawatan Pascaanestesi pada Resipien Transplantasi Ginjal - Kurniawaty, Juni (Jurnal Komplikasi Anestesi, 2021)
Renal transplantation is a principal therapy for end stage renal disease. Renal transplantation can decrease mortality and improve recipient quality of life substantially. However, immunosuppressant therapy and comorbid disease in those patients make perioperative management challenging. A good urine output is a usual sign of good allograft function. Postoperatively, recipient should have a slight positive fuid balance and higher blood pressures to maintenance adequate posttransplanted organ perfusion. Fluid replacement should consider urine output, insensible water loss dan volume status of the recipient. Goal of the management is to reduce fuid replacement gradually while maintain hemodynamic stability